The gourd and the cross : Daoism and Christianity in dialogue - Kim, Sŭng-hye, 1943- (Three Pines Press, 2014)
The Gourd and the Cross goes back to an actual dialogue, first published in Korean in 2003. Reflecting highly personal understanding and exploration, it correlates Dao and the reign of God, compares Jesus and the sage of the Daode jing, and matches ideas of freedom in the Zhuangzi and the New Testament. It also establishes a dialogue between Daoist mind-fasting and Christian unknowing, examines concepts of Eastern immortality versus Western egalitarianism, and discusses visions of nature and humanity in the two religions, both traditionally and in terms of modern ecology. It concludes with an.